THE IMPACT OF MASS MEDIA ON THE EMOTIONAL STATE OF ADOLESCENTS IN WARTIME - Melnyk, Iryna (Personality and environmental issues, 2026)
The purpose of the article is to provide a theoretical analysis and empirical study of the impact of mass media on the emotional state of adolescents in wartime. The article examines the essence of information and psychological influence, identifies the peculiarities of adolescents’ perception of media content, and outlines the main psychological consequences of destructive informational influence under conditions of armed conflict. Methodology. The study was conducted using a set of psychodiagnostic methods, including the “Level of Emotional Stability” test (E. Tarasov), the SAN method (well-being, activity, mood), the Four-Modal Emotional State Questionnaire (L. Rabinovich), and the Spielberger–Khanin Anxiety Inventory. An experimental approach was applied, comparing indicators of adolescents’ emotional state before and after exposure to informational video materials. Scientific novelty. The role of mass media as a factor of information and psychological influence in the context of hybrid warfare is substantiated. The study identifies specific features of adolescents’ emotional responses to war-related media content and demonstrates that intensive media exposure leads to decreased emotional stability, increased anxiety levels, and the intensification of negative emotional states such as fear, anger, and sadness. It is established that insufficient development of critical thinking increases adolescents’ vulnerability to destructive informational influences. Conclusions. It has been proven that mass media significantly affect the emotional state of adolescents in wartime, intensifying anxiety, emotional instability, and negative experiences. An increase in both state and trait anxiety, a decrease in mood, and reduced emotional stability after exposure to war-related media content were observed. The findings highlight the need to develop adolescents’ critical thinking, emotional regulation skills, and measures aimed at ensuring their information and psychological safety.